2016
DOI: 10.1371/journal.pone.0152019
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Japanese Version of the STarT Back Tool in Patients with Low Back Pain

Abstract: Background and ObjectiveThe STarT Back Tool uses prognostic indicators to classify patients with low back pain into three risk groups to guide early secondary prevention in primary care. The present study aimed to evaluate the psychometric properties of the Japanese version of the tool (STarT-J).MethodsAn online survey was conducted among Japanese patients with low back pain aged 20–64 years. Reliability was assessed by examining the internal consistency of the overall and psychosocial subscales using Cronbach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 30 publications
(44 reference statements)
2
28
1
Order By: Relevance
“…The Cronbach’s alpha coefficient for the STarT-G was 0.71, indicating a good internal consistency. This value was similar to that obtained for the Japanese 9-item STarT scale (0.75) 13. Concurrent validity was assessed by analyzing correlations between the STarT-G and pain NRS scores, which were moderately correlated with each other ( r = 0.34).…”
Section: Discussionsupporting
confidence: 81%
“…The Cronbach’s alpha coefficient for the STarT-G was 0.71, indicating a good internal consistency. This value was similar to that obtained for the Japanese 9-item STarT scale (0.75) 13. Concurrent validity was assessed by analyzing correlations between the STarT-G and pain NRS scores, which were moderately correlated with each other ( r = 0.34).…”
Section: Discussionsupporting
confidence: 81%
“…The results of the present study suggest the use of screening questionnaires to compensate for the low sensitivity of PT identification of psychological problems among patients. Some screening questionnaires for LBP prognosis have been proposed [28,29]. However, no study has shown the Japanese cutoff points for screening questionnaires that have high sensitivity to detect psychological problems.…”
Section: Clinical Implications and Research Agendamentioning
confidence: 99%
“…has generated great interest in developed countries, providing new hope that meaningful improvements in primary care for LBP are within reach. [14][15][16][17][18][19] Prior to widespread implementation, it would be valuable to know if the STarT Back strategy can be successfully translated to other settings. To determine if the STarT Back risk stratification strategy would succeed in the USA, we conducted the Matching Appropriate Treatments to Consumer Healthcare needs (MATCH) cluster randomized trial.…”
Section: Introductionmentioning
confidence: 99%